Four genera of Limoniidae (Diptera) new to Japan with descriptions of new species - Kato, Daichi (Zootaxa, 2022)
Four limoniid genera are added to Japan for the first time. Four new species, Crypteria nippon sp. nov., Dasymallomyia tachii sp. nov., Eupilaria japonica sp. nov., and Protohelius japonicus sp. nov. are described, and Dasymallomyia ditenostyla Alexander, 1964 is recorded from Japan for the first time. Images of the habitus and wings and drawings of the male and female terminalia are provided.